05 Negotiating Masculinity through Language: The Case of Pakistani Facebook Confession Pages (Journal of Gender and Social Issues, 2017)
This study aims to explicate the construction of male identity through language, and the corresponding embedded notions about gender roles and female gender stereotypes in Pakistani society, in relation to the posts on Pakistani Facebook Confession Pages. Social networking sites are being extensively used by youth for a myriad of purposes and analysis of posts on the Confession Pages included in the present study highlights significant aspects of language usage pertaining to 'gender contestation' and the underlying relations of power and male dominance. Adopting a critical discourse analysis framework, the analysis sheds light on three threads of discourse apparent in the selected posts: the discourse of romance, discourse of contention and discourse of discrimination.  The analysis shows that the discourse used by males to indicate female desirability is associated with complacency and in turn acts as a foil on which they establish their own masculinity – and dominance.
Keywords: Facebook Confession Pages; masculinity; discourse of romance; gender roles; stereotypes